Waray beauty writing at the margins and the poems in Oyzon's An Maupay ha mga Waray - Agustin, Efmer E. (2014)
Voltaire Q. Oyzon’s first Waráy poetry collection, An Maupay ha mga Waray (Our Virtue as Warays), bears the marks of protest and affirmation characteristic of postcolonial literatures. Though the poems in the collection may often be read as expressions and views of love and life, they also talk about the collective experience of the Waráy people, the trauma brought about by foreign colonization, and the imposition of the culture and language of “imperial Manila.” The collection asserts in several ways the magnificence of the Waráy language, dispelling the widely-accepted notion (among its own speakers included) of the “natural” inferiority of this tongue. It is an embodiment both of its author’s consciousness of the peripheral station given the Waráy language and literature and of its author’s efforts to undermine this station. The collection also offers itself as proof against the definition of “regional” literature as a depiction of “specific” life experiences seen from a “narrower” context, as opposed to “national” literature, which conveys “larger” issues and “broader” viewpoints— distinctions that Oyzon scoffs at. The collection, written in a “regional” language, demonstrates Waráy’s capacity to comprehend reality with lucidity and to articulate the universe with profundity and extensiveness similar to any other “national” literature. Solely through its publication, it also contradicts the proclamation once made that Waráy literature is dead. The poems provide an optimistic vision for the future of Waráy literature and bear the hope that the Waray-Waray people will be proud again of their own tongue and culture.
Keywords: Postcolonialism in literature; Oyzon, Voltaire -- Criticism and interpretation; Waray literature